PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - Suprihatmi Sri Wardiningsih, Dul Qodir, Y. Djoko Suseno & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2016)
The purpose of this study are to analyze: 1) effect of current ratio on firm value, 2) effect of debt to equity ratio on firm value, 3) effect of dividend policy on firm value, 4) effect of current ratio on firm value with dividend policy as moderation variables, 5 ) effect of debt to equity ratio on firm value with dividend policy as moderation variables. This type of research is empirical research conducted in real estate companies and properties companye are listed in the Indonesian Stock Exchange in 2011-2014. A sample of 42 companies with a total sampling technique. The type of data used quantitative and qualitative data. Source data used secondary data. Data collection technique used documentation. Analysis data used classical assumption test, multiple linear regression, t-test, F-test, coefficient determination and test the absolute difference. The results showed that current ratio has positive and significant effect on firm value. Debt to equity ratio has negative and significant effect on firm value. Dividend policy has positive but not significant effect on firm value. Dividend policy does not moderate the effect of the current ratio on firm value. Dividend policy does not moderate the effect of the debt to equity ratio on firm value. Keywords: current ratio, debt to equity ratio, dividend policy and firm value.